2012
DOI: 10.3168/jds.2011-4430
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bovine glucose transporter 1 kinetics and substrate specificities in Xenopus oocytes

Abstract: Glucose is an essential substrate for lactose synthesis and an important energy source in milk production. Glucose uptake in the mammary gland therefore plays a critical role in milk synthesis. Facilitative glucose transporters (GLUTs) mediate glucose uptake in the mammary gland. GLUT1 is the major facilitative glucose transporter expressed in bovine mammary gland and has been shown to localize to the basolateral membrane of mammary epithelial cells. GLUT1 is therefore thought to play a major role in glucose u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Xenopus oocytes expressing GLUT1 or GLUT3 show a similar increase in 2-DG accumulation, while water-injected oocytes show that 2-DG uptake from endogenous transporters in the oocyte membrane is negligible ( Fig 1B). Michaelis-Menten analysis of substrate saturation kinetics with GLUT1 resulted in a Km for 2-DG uptake of 9.5 mM ( Fig 1C), comparable with previous reports in the literature (Burant and Bell, 1992;Bentley et al, 2012). The uptake was inhibited by the GLUT inhibitor cytochalasin B. GLUT3 displays a similar cytochalasin B-dependent behavior with a Km of 2.6 mM ( Fig 1D).…”
Section: Affinity and Selectivity Comparison Between Glut1 And Glut3supporting
confidence: 88%
“…Xenopus oocytes expressing GLUT1 or GLUT3 show a similar increase in 2-DG accumulation, while water-injected oocytes show that 2-DG uptake from endogenous transporters in the oocyte membrane is negligible ( Fig 1B). Michaelis-Menten analysis of substrate saturation kinetics with GLUT1 resulted in a Km for 2-DG uptake of 9.5 mM ( Fig 1C), comparable with previous reports in the literature (Burant and Bell, 1992;Bentley et al, 2012). The uptake was inhibited by the GLUT inhibitor cytochalasin B. GLUT3 displays a similar cytochalasin B-dependent behavior with a Km of 2.6 mM ( Fig 1D).…”
Section: Affinity and Selectivity Comparison Between Glut1 And Glut3supporting
confidence: 88%
“…Kinetic assays revealed that FGT-1 has a K m of 2.8 mM for 2-DG, a non-metabolized glucose analog. This K m value is much lower than the K m reported for hGLUT1 (11.7 mM) or hGLUT4 (4.6 mM) [17,18], which is not surprising because C. elegans lives in a low glucose soil environment and may require cells to have transporters with a high affinity for glucose for its acquisition.…”
Section: Discussionmentioning
confidence: 58%
“…Oocytes were harvested from Xenopus laevis . The synthesized cRNA (2 µg/µL) or sterile water was injected into isolated mature oocytes (stage V and VI) following previously established procedures [17]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations